IMPLEMENTATION OF STRATEGIC MANAGEMENT OF MADRASAH PRINCIPALS IN FORMING STUDENTS' INDEPENDENT CHARACTER (Case Study at MTs. Muhammadiyah Ciasmara, Bogor Regency) and MTs. Mathlaul Anwar 2 Bogor City): IMPLEMENTATION OF STRATEGIC MANAGEMENT OF MADRASAH PRINCIPALS IN FORMING STUDENTS' INDEPENDENT CHARACTER (Case Study at MTs. Muhammadiyah Ciasmara, Bogor Regency) and MTs. Mathlaul Anwar 2 Bogor City) - Abdilah, Didih; Ahmad, Gofur; Hasanah, Hasanah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
The leadership of a Madrasah Principal is a crucial aspect of the educational process. Likewise, the Principals of MTs. Muhammadiyah Ciasmara in Bogor Regency and MTs. Mathlaul Anwar 2 in Bogor City play a central role in shaping the character of their students. Madrasah Principals hope that noble morals reflecting Islamic character will be instilled in their students. The focus of this research is developed in two focuses as follows: (1) How does the Principal of Madrasah develop a work environment to shape the character of students at MTs. Muhammadiyah Ciasmara, Bogor Regency and MTs. Mathlaul Anwar 2, Bogor City? (2) How does the Principal of Madrasah provide satisfactory services to shape the character of independence of students at MTs Muhammadiyah Ciasmara and MTs. Mathlaul Anwar 2, Bogor City? This research uses qualitative research.field research (field research). Data collection techniques used (1) Observation, (2) Interviews, (3) Documentation. In this research, the determination of research subjects uses the technique purposive samplingIn data collection, this study used Miles and Huberman's interactive model, namely: data collection, data reduction, data presentation, and conclusion drawing. In testing the validity of the data, the researcher used triangulation, namely source triangulation, method triangulation, and peer discussion. Researchers found various activities related to various self-development of students at MTs. Muhammadiyah Ciasmara, Bogor Regency and MTs. Mathlaul Anwar 2, Bogor City, namely: (1) That the Principal of the Madrasah in developing a work environment to form the character of independence of students at MTs. Muhammadiyah Ciasmara, Bogor Regency and MTs. Mathlaul Anwar 2, Bogor CityFirst, Providing Motivation,second, Placement of teachers according to their competencies,third, Conducting a Personal Approach from the Madrasah Principal to Teachers,Fourth, Instilling spiritual values ​​in the work environment. (2) The Head of Madrasah in providing satisfactory services to shape the character of students;First, cultivation of work discipline, Second, Professional Service,third, Awarding of awards to outstanding teachers,Fourth, Teacher involvement in madrasa activities,Fifth,Conduct academic supervision of teachers.